AMIGO2 Scales Dendrite Arbors in the Retina - Florentina Soto; Nai-Wen Tien; Anurag Goel; Lei Zhao; Philip A. Ruzycki; Daniel Kerschensteiner (Cell Reports, 2019)
Summary: The size of dendrite arbors shapes their function and differs vastly between neuron types. The signals that control dendritic arbor size remain obscure. Here, we find that in the retina, starburst amacrine cells (SACs) and rod bipolar cells (RBCs) express the homophilic cell-surface protein AMIGO2. In Amigo2 knockout (KO) mice, SAC and RBC dendrites expand while arbors of other retinal neurons remain stable. SAC dendrites are divided into a central input region and a peripheral output region that provides asymmetric inhibition to direction-selective ganglion cells (DSGCs). Input and output compartments scale precisely with increased arbor size in Amigo2 KO mice, and SAC dendrites maintain asymmetric connectivity with DSGCs. Increased coverage of SAC dendrites is accompanied by increased direction selectivity of DSGCs without changes to other ganglion cells. Our results identify AMIGO2 as a cell-type-specific dendritic scaling factor and link dendrite size and coverage to visual feature detection. : Soto et al. find that two retinal interneurons express the cell-surface protein AMIGO2. Deletion of Amigo2 causes dendrites of these neurons, but not others, to expand, preserving branching patterns and connectivity. Increased interneuron dendrite coverage is accompanied by enhanced response selectivity of retinal output neurons. Keywords: leucine-rich repeat protein, LRR, retina, dendrites, development, direction selectivity, starburst amacrine cell, rod bipolar cell